2019
DOI: 10.1371/journal.pone.0225905
|View full text |Cite
|
Sign up to set email alerts
|

A new finite element based parameter to predict bone fracture

Abstract: Dual Energy X-Ray Absorptiometry (DXA) is currently the most widely adopted non-invasive clinical technique to assess bone mineral density and bone mineral content in human research and represents the primary tool for the diagnosis of osteoporosis. DXA measures areal bone mineral density, BMD, which does not account for the three-dimensional structure of the vertebrae and for the distribution of bone mass. The result is that longitudinal DXA can only predict about 70% of vertebral fractures. This study propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 51 publications
(54 reference statements)
0
20
0
Order By: Relevance
“…In the last years, a new parameter based on FEM and named BSI has been introduced ( 53 ). The Authors demonstrated a good correlation between yield strain index (calculated by using the load causing the yield in each sample) and experimental yield measured on porcine vertebra samples.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last years, a new parameter based on FEM and named BSI has been introduced ( 53 ). The Authors demonstrated a good correlation between yield strain index (calculated by using the load causing the yield in each sample) and experimental yield measured on porcine vertebra samples.…”
Section: Introductionmentioning
confidence: 99%
“…However, just a few studies deal with the lumbar anatomic site. Recently, a new bone FEM structural DXA parameter named BSI, has been proposed in order to improve fracture risk prediction and take into account all the features involved in bone strength ( 53 ). Bone Strain Index calculation can be obtained in <10 s (=10 second) directly from images generated by DXA device ( 71 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new DXA-based parameter has been recently created, with the name of Bone Strain Index (BSI) [ 11 ]. This tool represent the analysis of a deformation index that is obtained by the use of finite element analysis from DXA images, and it is consistent with the mathematical model called Finite Element Model (FEM) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another recently developed bone structural parameter is the lumbar Bone Strain Index (BSI), a stress and deformation vertebral parameter derived from a finite element analysis of the lumbar DXA scan [16,17], that is based on a mathematical model called Finite Element Method (FEM) [18].…”
Section: Introductionmentioning
confidence: 99%